Modeling psychology in Islamic wealth management - Al-Abbadi, Ahmed Hamed; Abdullah, Adam (Canadian Center of Science and Education, 2017)
This paper proposes a conceptual framework for modeling psychology in Islamic wealth management. Incorporating psychology into finance would significantly contribute to our understanding of the behavior of individual investors as well as market behavior. Utilizing the findings of behavioral finance and financial therapy, along with industry mega-trends, Islamic wealth management could step further in fulfilling its ultimate objective of promoting social welfare. This is can be achieved by exploring and identifying the psychological factors that affect the clients' decision-making and then behaviorally and cognitively helping them to engage in socially-responsible investments, projects and initiatives. In operationalizing this model, financial advisors/wealth managers should adopt a comprehensive client discovery and profiling method and apply Fintech innovations in producing complex analytics and thereby enriching the client experience.